PENGARUH UKURAN PERUSAHAAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA STUDY EMPIRIS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI TAHUN 2019-2020 - Siti Suharni; Herry Purnomo; Tika Ayuni (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
This study aims to determine the effect of firm size and corporate governance mechanisms on earnings management in state-owned companies. This study uses quantitative methods. The data was obtained from secondary data from the annual reports of BUMN companies listed on the IDX during the 2019-2020 period. The sampling method used is purposive sampling method. The analysis technique used is multiple regression analysis with SPSS 16.00 for windows program. The results of this study indicate that the Firm Size variable and the Board of Commissioners Size variable have a significant effect on Earnings Management. While the variable Institutional Ownership, Board of Directors Size variable and Institutional Ownership variable have no significant effect on Earnings Management in BUMN Companies in 2019-2020.